Urban development beyond a centre-periphery dichotomy. An analysis of small and medium-sized towns in Denmark. - Christian Fertner; Høgni Kalsø Hansen; Lars Winther (European Journal of Spatial Development, 2024)
There is a growing European policy interest in small and medium-sized towns’ (SMSTs) potential to contribute to a more balanced territorial development. National policy in Denmark has only recently begun to address SMSTs directly. Often, SMSTs’ development is reduced to either being part of bigger functional urban regions or, in the case of rural areas, hidden behind larger regional development agendas. A key research question is therefore which development paths can we see beyond the growth-decline dichotomy. On the backdrop of this, the ESPON TOWN DENMARK project (2022) juxtaposed general trends of growth and decline in population and employment in Danish SMSTs to other aspects as demography, education, industry, service provision as well as regional position. We develop and apply an analytical typology adding more nuances to SMST’s development pathways.